2009
DOI: 10.1542/peds.2008-2281
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E Genotype Modifies the Risk of Behavior Problems After Infant Cardiac Surgery

Abstract: OBJECTIVE-The goal was to evaluate polymorphisms of the APOE gene as modifiers of neurobehavioral outcomes for preschool-aged children with congenital heart defects, after cardiac surgery.METHODS-A prospective observational study with neurodevelopmental evaluation between the fourth and fifth birthdays was performed. Attention and behavioral skills were assessed through parental report. RESULTS-Parents of 380 children completed the neurobehavioral measures. Child BehaviorChecklist scores for the pervasive deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 32 publications
3
81
3
Order By: Relevance
“…A previous study (Gaynor et al. 2009) also did not find a significant effect regarding ADHD specifically. However, this study was conducted using children of preschool age who were much younger than those of this study.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…A previous study (Gaynor et al. 2009) also did not find a significant effect regarding ADHD specifically. However, this study was conducted using children of preschool age who were much younger than those of this study.…”
Section: Discussionmentioning
confidence: 81%
“…Interestingly, these results in adolescents are opposite to what was found (Gaynor et al. 2009) in CHD patients of preschool age (i.e., the ε2 allele is deleterious while the ε4 allele is neuroprotective).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…50 In comparison with normative populations, survivors of infant heart surgery have more problems with reasoning, learning, executive function, inattention and impulsive behavior, language skills, and social skills. [51][52][53] The past decade has heightened awareness of neurocognitive challenges in children with CHD, and American Heart Association recommendations now provide guidance to pediatric caregivers about the need for regular screening for those at high risk. Nucleosome with histone octamer and DNA, with H3K4 methylation bound by CHD7, H3K27 methylation, and H2BK120 ubiquitination is shown.…”
Section: Neurodevelopment In Chdmentioning
confidence: 99%
“…1 Small studies at individual institutions have shown that children with CHD undergoing surgery in infancy have more problems with reasoning, learning, executive function, inattention and impulsive behavior, language skills, and social skills compared with peers without CHD. [2][3][4][5] Lower abilities in these areas may lead to poor school performance, strained interpersonal relationships, and behavior problems. Survivors of cardiac surgery in infancy are more likely than the general population to require remedial services, including tutoring and special education, as well as physical, occupational, and speech therapy.…”
Section: What This Study Addsmentioning
confidence: 99%